Effects of farming specialisation on grassland birds in Mediterranean High Nature Value farmland - Joana Santana; Pedro J. Leitão; Paulo Flores Ribeiro; Pedro Beja; Ângela Lomba; Rui Pedroso; Rui Morgado; Ricardo C. Martins; Inês Catry; Ana Teresa Marques; Luís Reino; Francisco Moreira (Global Ecology and Conservation)
The benefits of low-intensity mixed livestock-crop farming systems for Mediterranean farmland biodiversity have been widely documented. However, little is known about the effects of farming specialisation, even though the European Union's Common Agricultural Policy (CAP) has promoted the replacement of mixed systems by specialised livestock and crop systems. We investigated how specialisation affects birds in open farmland of southern Portugal, by analysing spatial associations between farming systems, land uses, and birds’ species richness and occurrence. We found a dominant landscape gradient contrasting specialisation in either sheep or cattle. The sheep system was positively related to woodland/shrubland-related species, Galerida larks and Melanocorypha calandra, while the cattle system was negatively related to these species. The specialised crop system, when associated with olive groves (< 10 % of the area), was negatively related to fallow-related species, M. calandra and Calandrella brachydactyla and positively so to overall species richness and that of woodland/shrubland-related species. Land uses had strong effects on birds, regardless of the farming systems in which they were embedded. Fodders were positively related to woodland/shrubland- and cereal-related species, Emberiza calandra and Cisticola juncidis. Rainfed grain cereals were positively related to cereal-related species, C. juncidis and Coturnix coturnix. Pastures were positively related to fallows- and ploughed-related species, M. calandra, Tetrax tetrax, and Galerida larks. Results suggest that programs for grassland conservation should consider both farming systems and land uses. CAP should promote diversified farming systems with reduced livestock densities along with high-quality habitats for grassland birds like pastures, fallows, rainfed grain cereals and semi-natural features.